Penerapan Sistem Informasi Akuntansi Penjualan Pada PT”X” Di Surabaya - Nadia Natalia Syahfitri; Wiratna Wiratna; Achmad Daengs GS; Diana Zuhroh; Sutini Sutini; Tjandra Wasesa; Heri Toni Hendro P (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research was conducted at PT”X” in Surabaya. The purpose of this study was to determine the sales accounting information system that has been running at PT”X” in Surabaya. PT”X” uses the cash of sales menthod. This research is a research using qualitative methods, using data sources, namely observation, interviews, documentation conducted at PT”X” in Surabaya. The method used is the descriptive method which is an analysis using data obtained by the author from several document related to the company. The results of this study indicate that PT”X” implements sales payments in cash with the method of paying before the goods are received and the methode of paying when the goods are received. The sales accounting information system at PT”X” in Surabaya still has a dual function between the sales function and the cash receipts function which is still carried out by the sales administration staff.